2016
DOI: 10.18632/aging.101092
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the Myc regulator Mtbp extends survival and delays tumor development in aging mice

Abstract: Alterations of specific genes can modulate aging. Myc, a transcription factor that regulates the expression of many genes involved in critical cellular functions was shown to have a role in controlling longevity. Decreased expression of Myc inhibited many of the deleterious effects of aging and increased lifespan in mice. Without altering Myc expression, reduced levels of Mtbp, a recently identified regulator of Myc, limit Myc transcriptional activity and proliferation, while increased levels promote Myc-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Different alleles of Hsd17b1 were found to be significantly associated with human longevity in females ( Scarabino et al, 2015 ). A single knockout of Mtbp in mice led to an extension of lifespan ( Grieb et al, 2016 ). Knockdown of Mrpl37 increased the lifespan of Caenorhabditis elegans by 41% on average ( Houtkooper et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different alleles of Hsd17b1 were found to be significantly associated with human longevity in females ( Scarabino et al, 2015 ). A single knockout of Mtbp in mice led to an extension of lifespan ( Grieb et al, 2016 ). Knockdown of Mrpl37 increased the lifespan of Caenorhabditis elegans by 41% on average ( Houtkooper et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…We examined a few other sequence changes at the positive selection sites in other mammals and found that only changes in beaver Mtbp were predicted to be deleterious ( Figure S11D ), which may contribute to its cancer resistance. Haploinsufficiency of Mtbp in mice delays spontaneous cancer development and extends lifespan by enhancing Tp53 function ( Grieb et al, 2016 ). Our hypothesis on the decreased function of Mtbp, due to deleterious mutations, is supported by the lower expression of Mtbp in beavers than in mice ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, increased MTBP expression is also able to promote neurosphere formation [ 19 ]. Additionally, compared to wild-type littermates, Mtbp heterozygous mice had reduced spontaneous cancer development [ 11 ]. Taken together, the data indicate that MTBP has oncogenic activity.…”
Section: Mtbp Promotes Cellular Proliferation and Transformationmentioning
confidence: 99%
“…Consistent with its oncogenic role, MTBP has been shown to be overexpressed in a wide range of human cancers, where it is associated with poor patient outcomes in the majority of malignant contexts [ 4 , 8 , 9 , 10 ]. Moreover, suppression of MTBP expression in malignant cells or expression of a mutant with apparent dominant-negative activity demonstrated MTBP-directed therapeutics could have broad applicability as cancer therapies and extending patient survival [ 3 , 4 , 8 , 11 ], similar to its binding partner MYC. Herein, we review these advances and raise lingering questions.…”
Section: Introductionmentioning
confidence: 99%
“…MTBP is an oncogenic protein that was found to be overexpressed in different human cancers and to promote c-MYC driven transformation in conjunction with Reptin and Pontin (Grieb et al, 2014). Moreover, mice expressing reduced levels of MTBP or c-MYC were found to have a significant delay in spontaneous cancer development, particularly prominent in the haematopoietic compartment (Grieb et al, 2016).…”
Section: Reptin Regulates C-myc Protein and Transcript Levelsmentioning
confidence: 99%